If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7y + 4) + -1(-6y + -5) = 1 Reorder the terms: -1(4 + 7y) + -1(-6y + -5) = 1 (4 * -1 + 7y * -1) + -1(-6y + -5) = 1 (-4 + -7y) + -1(-6y + -5) = 1 Reorder the terms: -4 + -7y + -1(-5 + -6y) = 1 -4 + -7y + (-5 * -1 + -6y * -1) = 1 -4 + -7y + (5 + 6y) = 1 Reorder the terms: -4 + 5 + -7y + 6y = 1 Combine like terms: -4 + 5 = 1 1 + -7y + 6y = 1 Combine like terms: -7y + 6y = -1y 1 + -1y = 1 Add '-1' to each side of the equation. 1 + -1 + -1y = 1 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 1 + -1 -1y = 1 + -1 Combine like terms: 1 + -1 = 0 -1y = 0 Solving -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = 0 Simplifying y = 0
| 40-5x=x-8 | | 4a+7+3a=-14 | | 54+16x-x^2=0 | | 2x-2y+8=0 | | 13(6c-1)-18=76c+13 | | 15=7x-13 | | 10-14xy+5x-21= | | ln(x)+ln(x+8)=6 | | 7(y-3)=4y-36 | | x^2+14x+58=0 | | 12-7=-2 | | 9ln(x+9)-7ln= | | 4x^4=41x^2-100 | | 12x^2-15+11x=0 | | 3x^2-x-4=o | | 8x^2+1=3x | | x+13-28+5=177 | | 3t-8=4(t+7) | | 6y-8=4y | | x^2+13x+41= | | 3x-39=3 | | 3q^2=5q+2 | | 5r+10=45 | | 9x-14=49 | | (8a^3)(b^3)+(27a^6)= | | 2x(x+4)(6)=16 | | 2w-5w=12 | | -5(3p+4)-10=4(4p+8) | | 8=y-10 | | -86+5y+6=5(3y-3)-5 | | 7(6x-8)=70 | | 5x^3+20x^2+20= |